POTENSI CADANGAN KARBON PADA SISTEM AGROFORESTRI BERBASIS KARET - Sahuri Sahuri (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
Rubber tree (Hevea brasilliensis Muell. Arg) has a very big role in economy and absorption of CO2 through the implementation of rubber based agroforestry. This study aims to determine the potential for carbon sequestration in rubber based agroforestry. The experiment was conducted at Sembawa Research Station from January until April 2016 on immature rubber plantation of IRR 112 clone 1 year old, with spacing of 6 m x 3 m (550 tree/ha). The experiment implements randomized block design, three replications. The treatments applies six planting patterns i.e PT1: rubber + peneaple, PT2: rubber + sorghum, PT3: rubber + upland rice, PT4: rubber + corn, PT5: rubber + soybean, and PT6: monoculture rubber. Data are statistically analyzed using ANOVA, followed by DMRT at the level of 5%. Measurements of carbon stock consist of rubber biomass, intercrops biomass, and soil organic matter. The results show that the average of carbon stocks in rubber based agroforestry on 1 year old rubber trees is 2.15 tons C/ha significantly higher than monoculture rubber system, about 0.57 tons C/ha. This is due to the carbon enrichment from rubber intercrops about 1.57 tons C/ha/planting season.